Production and use of arbuscular mycorrhizal fungi inoculum in sub-Saharan Africa: challenges and ways of improving - Mukhongo, Ruth Wilhem; Tumuhairwe, J.B.; Ebanyat, Peter; AbdelGadir, Abdel Aziz H.; Thuita, Moses N.; Masso, C. (Science Alert, 2016)
Use of inorganic fertilizer is an essential practice to optimize crop productivity in the poor fertility soils in sub-Saharan Africa, but it has been linked to high cost of crop production, contamination of surface and/or ground water by nitrate leaching and eutrophication of surface water by phosphate run-off. Besides, secondary effects on soil biotic community and soil impoverishment have weakened cropping systems making them increasingly dependent on external chemical fertilizers. Efficient plant nutrition management should ensure both enhanced and sustainable agricultural production and safeguard the environment. Improved production and adoption of bio-inoculants such as arbuscular mycorrhizal fungi is an emerging soil fertility management practice with potential to increase and cheaply improve crop yields. Arbuscular mycorrhizal fungi inoculum production and adoption in sub-Saharan Africa smallholder systems is however, still limited mainly by research capacity and technological challenges. This study provides the state of the art in production and use of the technology and highlights the challenges and opportunities for its advancement. To experience the benefits of arbuscular mycorrhizal fungi, sound investment on research in low input systems and technical support from the government, the public and the private sectors should be considered. Nevertheless, adequate training of extension workers, agro-dealers and smallholder farmers through agricultural, academic and research institutions will solve the challenges of production and adoption of arbuscular mycorrhizal fungi inoculum technology hence improve crop production.